Fundamental Analysis Of Nickel Companies’ Stock Prices Listed On The Indonesia Stock Exchange For The Period 2020–2024 - Anwar Ramli; Febrianty Muliana Saputri; Syardiansyah; Putri Yulinar; Salsabilah (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study was conducted to examine the influence of financial ratios on stock price movements of nickel mining companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Indicators used in the analysis include Return on Equity (ROE), Earnings per Share (EPS), Debt to Equity Ratio (DER), Price Earning Ratio (PER), and Price to Book Value (PBV), which represent aspects of profitability, solvency, and market valuation of the company. A quantitative approach was used in this study by processing secondary data in the form of annual financial reports from issuers that met the selection criteria. The results showed that each company has a different performance pattern based on the five ratios, where ANTM shows stability and growth, TINS ​​presents high volatility, while INCO excels in a conservative financial structure. These findings are expected to serve as a reference for investors in making decisions based on fundamental analysis, as well as provide additional references for management and academics in assessing the dynamics of the nickel industry in Indonesia.